2015
DOI: 10.3168/jds.2015-9418
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-24 can control triacylglycerol synthesis in goat mammary epithelial cells by targeting the fatty acid synthase gene

Abstract: In nonruminants it has been demonstrated that microRNA-24 (miR-24) is involved in preadipocyte differentiation, hepatic lipid, and plasma triacylglycerol synthesis. However, its role in ruminant mammary gland remains unclear. In this study we measured miR-24 expression in goat mammary gland tissue at 4 different stages of lactation and observed that it had highest expression at peak lactation when compared with the dry period. Overexpression or downregulation of miR-24 in goat mammary epithelial cells (GMEC) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Total RNA was extracted from cultured cells with Trizol reagent (Invitrogen) according to the manufacturer's instructions. The mature miRNA expression level was determined with S‐Poly(T) assay (Kang et al, ) and the detail information for S‐Poly(T) assay was reported previously (Wang et al, ). All the primers used for miRNA RT‐qPCR are listed in Additional file 1.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from cultured cells with Trizol reagent (Invitrogen) according to the manufacturer's instructions. The mature miRNA expression level was determined with S‐Poly(T) assay (Kang et al, ) and the detail information for S‐Poly(T) assay was reported previously (Wang et al, ). All the primers used for miRNA RT‐qPCR are listed in Additional file 1.…”
Section: Methodsmentioning
confidence: 99%
“…A role for miR-152 in the development and lactation of mammary glands in dairy cows through regulation of DNMT1 gene has been suggested10. MiR-24 was shown to control triacylglycerol synthesis in goat mammary epithelial cells by targeting the FASN gene17. Overexpression of miR-30b in the developing mammary gland of transgenic mouse caused lactation defects such as reduced size of alveolar lumen, defect of the lipid droplet and growth defect in pups as well as delayed involution, thus suggesting the importance of miR-30b in mammary gland biology and how the deregulation of only one miRNA could affect lactation and involution18.…”
mentioning
confidence: 99%
“…These data suggest differential posttranscriptional regulation of FASN among species due to (1) higher translation repression or degradation of mRNA in cows, which affects FASN protein synthesis and mRNA stability (Semenkovich et al, 1993) and may involve microRNA such as miR-145 (Wang et al, 2017) and miR-24 (Wang et al, 2015) that target FASN mRNA; (2) different ubiquitination of lysine or phosphorylation in sites of the protein sequence affecting protein activity (Wakil et al, 1989;Jensen-Urstad and Semenkovich, 2012); or (3) other mechanisms. In addition to the multifunctional enzyme FAS, the biosynthesis of de novo FA requires considerable amounts of reducing equivalents in the form of NADPH.…”
mentioning
confidence: 99%